2006
DOI: 10.1002/app.23593
|View full text |Cite
|
Sign up to set email alerts
|

Study of rheological behavior of hydrophobically modified hydroxyethyl cellulose

Abstract: ABSTRACT:Hydrophobically modified hydroxyethyl cellulose (BD-HAHEC) was synthesized by the macromolecular reaction of hydroxyethyl cellulose (HEC) with bromododecane (BD). Study of the effects of polymer concentration, shear rate, temperature, and electrolytes on the rheological behavior of BD-HAHEC indicated that the polymers had high viscosity, excellent viscosity retention in brine water, good thermal stability, and surface activity. Furthermore, investigation of the micromorphology of BD-HAHEC solutions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Now there have appeared large quantities of literatures concerning of this kind of polymers [23][24][25][26][27][28][29]. After partial hydrophobization, the cellulose derivatives can be dissolved in common organic solvents, which makes the further functionalization much easier and better controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Now there have appeared large quantities of literatures concerning of this kind of polymers [23][24][25][26][27][28][29]. After partial hydrophobization, the cellulose derivatives can be dissolved in common organic solvents, which makes the further functionalization much easier and better controlled.…”
Section: Introductionmentioning
confidence: 99%
“…in 2005 reported hydroxyethyl cellulose in combination with bromododecane increased viscosity and caused thermal stability. [10] Gallardo et al . in 2006 investigated rheological properties of ethylcellulose latex.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in viscosity of the composite dispersion might have been caused by a reduction of intra-molecular hydrogen bonding of chitosan and a decrease in hydrogen-bonded hydration of chitosan, while heating did not affect the hydration of magnesium aluminum silicate, because magnesium aluminum silicate dispersions were prepared and hydrated using hot water in the preparation process (16). Li et al in 2005 reported that hydroxyethyl cellulose in combination with bromododecane increased viscosity and caused thermal stability (17). …”
Section: Discussionmentioning
confidence: 99%